The Mousterian industry in Dalmatia, Croatia - Karavanić, Ivor (Array, 2004)
The characteristics of Mousterian industry in Dalmatia (south Croatia) are little researched although rich lithic material has been collected on the surface of open-air sites. The only systematicaly excavated Mousterian cave site in the region, with clear stratigraphic context, is Mujina Pećina. Non-Levallois and Levallois debitage items have been found in several levels of the cave. Generally, Mousterian people of Dalmatia modify their lithic technology to effectively exploit local raw material sources. Tool assemblages are characterized by small tools (so-called Micromousterian) dominated by denticulates and notched pieces, like in other late Mousterian sites of Eastern Adriatic region. There are notable differences in tool typology between late Mousterian of the Eastern Adriatic region and Pontinian in west central Italy.